Different dynamic movements of wild‐type and pathogenic VCPs and their cofactors to damaged mitochondria in a Parkin‐mediated mitochondrial quality control system. (12th November 2013) - Kimura, Yoko; Fukushi, Junpei; Hori, Seiji; Matsuda, Noriyuki; Okatsu, Kei; Kakiyama, Yukie; Kawawaki, Junko; Kakizuka, Akira; Tanaka, Keiji
<x xml:space="preserve">Abstract</x> VCP/p97 is a hexameric ring‐shaped AAA+ ATPase that participates in various ubiquitin‐associated cellular functions. Mis‐sense mutations in VCP gene are associated with the pathogenesis of two inherited diseases: inclusion body myopathy associated with Paget's disease of the bone and front‐temporal dementia (IBMPFD) and familial amyotrophic lateral sclerosis (ALS). These pathogenic VCPs have higher affinities for several cofactors, including Npl4, Ufd1 and p47. In Parkin‐dependent mitochondrial quality control systems, VCP migrates to damaged mitochondria (e.g., those treated with uncouplers) to aid in the degradation of mitochondrial outer membrane proteins and to eliminate mitochondria. We showed that endogenous Npl4 and p47 also migrate to mitochondria after uncoupler treatment, and Npl4, Ufd1 or p47 silencing causes defective mitochondria clearance after uncoupler treatment. Moreover, pathogenic VCPs show impaired migration to mitochondria, and the exogenous pathogenic VCP expression partially inhibits Npl4 and p47 localization to mitochondria. These results suggest that the increased affinities of pathogenic VCPs for these cofactors cause the impaired movement of pathogenic VCPs. In adult flies, exogenous expression of wild‐type VCP, but not pathogenic VCPs, reduces the number of abnormal mitochondria in muscles. Failure of pathogenic VCPs to function on damaged mitochondria may be related to the pathogenesis of IBMPFD and ALS.